1998
DOI: 10.1152/ajplung.1998.275.4.l836
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of heat shock protein-70 protects A549 cells against hyperoxia

Abstract: Acute and chronic lung injury secondary to hyperoxia remains an important complication in critically ill patients, and, consequently, there is interest in developing strategies to protect the lung against hyperoxia. Heat shock proteins (HSPs) confer protection against a broad array of cytotoxic agents. In this study, we tested the hypothesis that increased expression of the 70-kDa HSP (HSP70) would protect cultured human respiratory epithelium against hyperoxia. Recombinant A549 cells were generated in which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 15 publications
5
55
1
1
Order By: Relevance
“…For example, addition of recombinant HSP-70 has been shown to inhibit cytochrome C/dATP-mediated caspase activation (41) and to block cell death via reduced p38 kinase activation (42). In addition, an overexpression study in human lung adenocarcinoma cells demonstrated a specific role for HSP-70 in blocking hyperoxia-mediated lipid peroxidation and cell death (43). Despite the ability of HSP-70 overexpression to protect HK-2 cells, blocking of HSP-70 upregulation with siRNA did not inhibit the protective effect of heat shock.…”
Section: Discussionmentioning
confidence: 98%
“…For example, addition of recombinant HSP-70 has been shown to inhibit cytochrome C/dATP-mediated caspase activation (41) and to block cell death via reduced p38 kinase activation (42). In addition, an overexpression study in human lung adenocarcinoma cells demonstrated a specific role for HSP-70 in blocking hyperoxia-mediated lipid peroxidation and cell death (43). Despite the ability of HSP-70 overexpression to protect HK-2 cells, blocking of HSP-70 upregulation with siRNA did not inhibit the protective effect of heat shock.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, induction of Hsp70 by thermal stress protected cultured murine lung epithelial cells and bovine pulmonary artery endothelial cells from oxidant-mediated injury (11,129). Overexpression of Hsp70 via stable transfection also protects lung epithelial cells from the deleterious effects of hyperoxia (130) and peroxynitrite (9,131). Perhaps more compelling, direct delivery of the mature Hsp70 protein using a Tat-Hsp70 protein protects HSF1 null fibroblasts, which lack the intrinsic ability to mount a stress response and are therefore susceptible to hyperoxia-mediated cell death (132), against the deleterious effects of hyperoxia (133).…”
Section: Hsp70mentioning
confidence: 93%
“…Hsp70 is the most highly induced stress protein in cells and tissues undergoing the stress response (3), and is known to be induced in patients with a variety of critical illnesses or injuries (140)(141)(142)(143). Microinjection of anti-Hsp70 antibody into cells impairs their ability to achieve thermotolerance (144), and increased expression of Hsp70 by gene transfer/transfection has been demonstrated to confer protection against in vitro toxicity secondary to lethal hyperthermia (145), endotoxin (8), nitric oxide (9), hyperoxia (130), and in vivo ischemia-reperfusion injury (146)(147)(148). In addition, in vitro delivery of mature Hsp70 into the intracellular compartment has been shown to protect fibroblasts against lethal thermal injury and hyperoxia (133), and neuronal cells against nitrosative stress and excitotoxicity (149).…”
Section: Stress Proteins and Cytoprotectionmentioning
confidence: 99%
“…These include direct oxidative damage (i.e., hydrogen peroxide or hypoxia reperfusion injury) as well as a variety of other stresses in which generation of ROS is implicated in cytotoxicity (i.e., chemotherapeutic agents, heat stress, cytokines) (Park et al, 1998;Preville et al, 1998;Wong et al, 1998;Chen et al, 1999;Creagh and Cotter, 1999;Komatsuda et al, 1999;Baek et al, 2000;Ding and Keller, 2001). In addition, elevated Hsp expression not only improves cell survival, but also reduces the oxidative damage to proteins, DNA, and lipids (Su et al, 1999;Yamamoto et al, 2000;Park et al, 1998).…”
Section: Heat Shock Protein (Hsp) Expressionmentioning
confidence: 99%